ANESTESI SPINAL THORAKAL KONTINYU PADA WANITA DENGAN GASTROINTESTINAL STROMAL TUMOR (GIST) GASTER - Bagas Adji Prasetyo; Imam Ghozali; Agung Ikhssani (POLTEKKES KEMENKES MEDAN, 2021)
Gastrointestinal Stromal Tumor (GIST) is one of the most common primary mesenchymal gastrointestinal tract tumors (sarcomas), which is caused by DNA mutations that lead to overactivation of the thyrokinase enzyme. The most frequently symptoms complained by patients was abdominal pain, blood in the stool, and symptoms of anemia. Surgery is the defiitive treatment fot GIST, where partial resection is the most common practice. Continous Spinal Anesthesia (CSA) technique is an anesthetic technique that is suitable for abdominal surgery with a low failure rate. A 56 years old woman presented with recurrent blood in the stool since 2 years before being admitted to the hospital accompanied by a painful mass in the upper left abdomen. Patient came in compos mentis state, blood pressure 110/70 mmHg, pulse rate 18x/minutes, respiratory rate 18x/minutes, temperature 36,5°C. Physical examination of the abdomen revealed no abnormalities and no palpable mass. A CT scan showed an impression of an intraluminal gastric mass, suggesting a Gastrointestinal Stromal Tumor (GIST).From the endoscopic examination, there was a rounded-mass on the gastric corpus with diameter of 5 cm then concluded the patient’s diagnosis was gastric GIST and partial gastrecyomy was managed. Good preoperative, intraoperativem and postoperative management will give better outcome. In postoperative statem patient condition was stable without complication.